A new and working petroleum source rock on the UK Continental Shelf (Upper Permian, offshore Yorkshire). (November 2020) - Słowakiewicz, Mirosław; Gluyas, Jon; Kowalski, Adam; Edwards, Thomas; Słama, Samuel; Mawson, Mike; Tucker, Maurice E.; Scovell, Paul; Polonio, Israel
Abstract: We report on the discovery of oil from the Boulby Mine and its likely productive source rock from Yorkshire in NE England, located to the west (<30 km) of the newly licensed petroleum exploration areas in the vicinity of the Mid-North Sea High. Oil samples from the mine, dripping out of halite in the roof, have likely been generated from Zechstein Group Kirkham Abbey Formation (KAF) sapropelic carbonate rock as indicated by aliphatic and aromatic hydrocarbon biomarkers. Other potential source rocks of Carboniferous (Westphalian, Namurian, Viséan coals and mudrocks) and Jurassic (the Jet Rock, Bituminous Shales, Kimmeridge Clay Formation) age are ruled out on the basis of organic geochemical data. Boulby oil was generated in the peak-to-late oil-window and it is characterised by the high abundance of C32 and C34 homohopanes, slight even-over-odd predominance (EOP) of C20-25 n -alkanes indicating restricted carbonate-evaporite depositional conditions, and C29 ethyl-diacholestane 20 S likely implying a clay-rich source rock. The structural framework and tectonic history of the Permian strata reveal the presence of several fault systems which served as conduits for migrating petroleum. Similar Zechstein-sourced oil is known from Poland and Germany, but the occurrence at Boulby is the first positive identification of oil derived from Zechstein source rock in the North Sea area. The Boulby oil is reservoired in Zechstein 3 (Z3) Brotherton Formation dolomite and sealed by Z3 evaporite rocks. The proven oil occurrence at Boulby has significant implications in terms of reducing the risk of a lack of oil mature source rock for acreage offered in the neighbouring North Sea during the UK's 30th and 31st licensing rounds. Highlights: A new and working petroleum source rock on the UK Continental Shelf. Boulby oil seeping from rock-salt fractures derives from sapropelic dolomite. A carbonate-evaporite depositional setting is confirmed.